Depiction of a monkey eating a fruit - Temples of India Project Team (Jio Institute, 2024)
The south face of the sukanasa (antefix above the roof of the kapila) shows a monkey sitting on a pedestal just above the balcony scene. The monkey is depicted eating fruit, with a noteworthy expression featuring large, bulging circular eyes and an open mouth. There are many temples in which animals are depicted. As monkeys are notorious in nature, they are mostly shown jumping and climbing but here, these actions are not depicted. Rather, the monkey is shown seated alone, peacefully eating a fruit, which makes it a unique representation.